The Role of SMAD2/3 in Human Embryonic Stem Cells - Yang, Jie; Jiang, Wei (Frontiers in Cell and Developmental Biology, 2020)
Human embryonic stem cells (hESCs) possess the potential of long-term self-renewal and three primary germ layers differentiation, and thus hESCs are expected to have broad applications in cell therapy, drug screening and basic research on human early embryonic development. Many efforts have been put to dissect the regulation of pluripotency and direct differentiation of hESCs. TGFβ/Activin/Nodal signal pathway critically regulates pluripotency maintenance and cell differentiation through the main signal transducer SMAD2/3 in hESCs, but the action manners of SMAD2/3 in hESCs are sophisticated and not documented yet. Here we review and discuss the roles of SMAD2/3 in hESC pluripotency maintenance and differentiation initiation separately. We summarize that SMAD2/3 regulates pluripotency and differentiation mainly through four aspects, (1) controlling divergent transcriptional networks of pluripotency and differentiation; (2) interacting with chromatin modifiers to make the chromatin accessible or recruiting METTL3-METTL14-WTAP complex and depositing m6A to the mRNA of pluripotency genes; (3) acting as a transcription factor to activate endoderm-specific genes to thus initiate definitive endoderm differentiation, which happens as cyclin D/CDK4/6 downstream target in later G1 phase as well; (4) interacting with endoderm specific lncRNAs to promote differentiation.